The Use of Foreign Language Learning Strategies in English and French - Orrego, Luz Mery; Díaz Monsalve, Ana Elsy (Íkala, Revista de Lenguaje y Cultura, 2010)
Objective: To identify conceptions about learning held by students and teachers in the undergraduate Foreign Language Teaching program at the University of Antioquia School of Languages and the frequency with which students use learning strategies to develop communicative competence in English and French. Method: An exploratory and descriptive study was conducted using qualitative and quantitative method. Students and teachers participated in semi-structured interviews individually and in groups, and the students’ self-assessment of their learning process was analyzed. Students’ learning strategies were described using the questionnaire ’’Strategy Inventory for Language Learning’’ (version 5.1, Oxford, 1990).Results: For the students, learning is an intellectual development process that requires the use of skills specific to a foreign language. Teachers’ conceptions can be classified under four theories of learning: behaviorist, psycholinguistic, pragmatic, and sociocultural. Regarding the use of learning strategies, results show that affective and memory strategies are the least frequently used, whereas cognitive, social, and compensation strategies are the most frequently used. Conclusions: The qualitative analysis of the students’ and teachers’ conceptions indicates that there are differences in the use of learning strategies between the two languages. However, the quantitative results of the study evidence that, in both English and French, students use learning strategies with the same frequency and in the same way. Received: 01-09-09 / Accepted: 04-03-10 How to reference this article: Orrego, L. M. & Diaz Monsalve, A. E. (2010). Empleo de estrategias de aprendizaje de lenguas extranjeras: inglés y francés. Íkala.15(1), pp.105-142.